Fizikas priekšmeta programma vidusskolas apvienotajās klasēs - Pūriņa, Anna (Latvijas Universitāte, 2013)
Darba mērķis ir izstrādāt vidusskolas fizikas mācību priekšmeta prigrammas varianta sturktūras plānojumu un īstenošanas pamatprincipus vidusskolas apvienotajās klasēs. Darba pirmajā daļā apzināti tematiskie materiāli par fizikas priekšmeta būtību un sūtību vispārizglītojošā vidusskolā un fizikas satura pasniegšanas metodēm apvienotajās klasēs. Darba otrajā daļā izstrādāts mērķis: izstrādās vidusskolas fizikas mācību priekšmeta programmas varianta struktūras plānojumu un īstenošanas pamatprincipus apvienotajās klasēs vidusskolā. Divu tematu izstrādnes pārbaudītas pedagoģiskajā procesā. Prakstiskais pētījums diplomdarbā daļēji apstiprināja izvirzīto hipotēzi. Izstrādāto darbu ir iespējams izmantot,plānojot un vadot fizikas stundas apvienotajās klasēs vidusskolā. Atslēgas vārdi: mācību process, mācību metodes, fizikas mācību satura tematiskais plānojums, apvienotās klases.

Graduation thesis was worked out in the Faculty of Education, Psychology and Art of the University of Latvia, Adult Education Centre in collaboration with the Faculty of Physics and Mathematics of the University of Latvia. The thesis contains 50 pages - Introduction (2 pages), two parts (14 and 31 pages), Conclusion (2 pages), as well as the List of references (26 sources) and the Supplement (4 units). 10 tables are inserted. The aim of the thesis is to develop a possible structural plan and guidelines for implementing teaching of physics in secondary schools combined classes. In Part 1 the existing thematic materials have been identified, especially emphasizing the nature and mission of physics in general education secondary school and teaching methods of physics in combined classes. In Part 2 the following aim is carried out: develop a possible structural plan and guidelines for implementing teaching of physics in secondary schools combined classes. The effectiveness of two of developed topics was tested in teaching process. The practical study of this thesis confirmed the hypothesis only partially. This graduation thesis may be used for planning and teaching physics in combined classes in secondary education. Key words: learning process, teaching methods, the thematic planning of physics classes, combined classes.
The physics curriculum in the secondary school combined classes
Keywords: Pedagoģija